Triadic closure, homophily, and reciprocation: An empirical investigation of social ties between content providers - SONG, tingting (Institutional Knowledge at Singapore Management University, 2019)
In social media, a content provider can initiate outgoingties to other providers to promote their content, thus inviting reciprocalpromotion. We investigate how the reciprocation benefit for the initiatingprovider is affected by homophily and triadic closure, the two major mechanismsof tie formation. Specifically, we examine how the increase in subscribers and viewershipof the initiating provider’s content attributable to the responding providers’reciprocation is moderated by common ties and content similarity between thetwo linked providers. Using a panel data on 27,356 YouTube video providers, wespecify a switching regression model toestimate the influence of content similarity and common ties on reciprocationimpact while correcting for their influence on reciprocation probability. Confirmingthat reciprocation is generally beneficial for the initiator, we find thatalthough content similarity and common ties increase reciprocation probability,they reduce the reciprocation benefit for the initiator in terms of subscribergrowth. We also find a positive interaction effect between content similarityand common ties on reciprocation impact, reducing their individual effects.Combining their respective influence on reciprocation probability and benefit,we further examine how content similarity and common ties affect the expectedbenefit for the initiator and derive practical implications for contentproviders and social media platforms.